Русинський рух у сучасній Румунії: ідентифікація, структура, рефлексії - Зан, М. (Народна творчість та етнологія, 2011)
In the article considered the evolution of the Ruthenian movement in modern Romania, who went public and political arena in the country at the beginning of the XXI century. According to the results of population census 2002 found out the specifics of Rusyn identity. The questions of parliamentary representation of Rusyns analyzed through the public activity of Gheorghe Firczak and Cultural Union of Rusyns in Romania. The ambiguous evaluations of Ruthenian movement in ethnographic field of Maramureş County are illustrated. The author concludes amorphous of Ruthenian movement in Romania compared to the Prešov Region or Transcarpathia and disparity of mobilization (situational) vector of its leaders and primordial (Ukrainian) essence of his «unconscious recipients». În articol este analizată evoluţia mişcării rutene din România contemporană, care a avansat în arena social-politică din ţară la începutul sec. XXI. Este evedenţiat specificul indentităţii rutene conform rezultatelor recensământului populaţiei din 2002. E analizată chestiunea reprezentării parlementare a rutenilor prin activitatea liderului public Gheorghe Firczak şi Uniunei Culturale a Rutenilor din România. E ilustrată conceperea diferită a mişcării rutene în terenul etnografic Maramureşan. Autorul conclude că mişcarea ruteană din România în comparaţie cu regiunile Preaşiv şi Transcarpatică e amorfă, iar vectorul forţei de mobilizare (situative) a liderilor săi deasemeni nu coincide ca şi esenţa primordială a «recipienţilor inconştienţi»